Language and Behavior: A Philosophy of Linguistic Habits in Everyday Life - Ni Luh Made Anitasari (Indonesian Journal of Foreign Language Studies, 2026)
Abstract Language functions not only as a medium of communication but also as a performative force that shapes patterns of thought, behavior, and social interaction in everyday life. This study aims to examine how habitual language use influences actions, emotional responses, social relations, and identity through a philosophy of language perspective, particularly speech act theory (Austin and Searle), pragmatics, and linguistic constructivism. This research employs a qualitative design using philosophical discourse analysis. Data were collected from everyday spoken and digital interactions through observation, semi-structured interviews, and documentation of recurring linguistic expressions. Data validity was ensured through triangulation across sources and contexts. The findings indicate that repeated linguistic patterns possess performative power that actively constructs behavioral tendencies, emotional orientations, social norms, and self-identity. Language does not merely reflect reality but participates in shaping and directing it. These findings highlight the urgency of ethical awareness in everyday language use, especially in digital communication, to foster more reflective, respectful, and constructive social interactions.